On the impacts of EEC beef preferences for Kenya and Botswana - Massow, V.H. von (1983)
Examines the beef sectors in Kenya and Botswana with regard to the impacts of EEC beef preferences and the net effects of both preferences and export policy. Discusses the world markets for beef, benefits of preferential exports, welfare effects of preference, comparative advantage of beef production, coefficients of protection for the beef sectors and domestic resource costs for beef production in both countries.